2D materials for lithium ion batteries - Muhd Iszaki Patdillah (Nanyang Technological University, 2018)
Nanosizing and nanostructuring from bulk crystal has led to interesting properties that appeal in Lithium energy storage research. The properties include having a larger surface area for energy storage and shorter diffusion length for fast electron transport. The project will be focusing on the investigation of a class of materials that is known as Metal thiophosphate. Bulk crystals of MnPS3 was exfoliated into high yield of nanosheets which served as an anode for the Lithium energy storage. It was then further characterized to obtain its structure morphology and thickness. The report also includes information on the mechanism of the different stages of Lithium energy storage. Also, the comparison of nanomaterials with respect to the desired properties as well as materials that had already been commercialized. The changes in morphology observed using the characterization technique from bulk MnPS3 to 2D nanosheets through exfoliation helped improve the performance of the material in Lithium energy storage. This includes having a higher storage surface area, having a uniform crystalline region and higher rate of ions exchange transport due to the reduction in thickness with shorter diffusion length. The changes in thickness does not affect the microstructure of the compound as the material remain to be stable and there are no drastic changes to the elements in the compound. This can be seen in XRD analysis where the prominent peaks are still present and the consistency of the element distribution can be seen using the EDX elemental analysis. From the electrochemical measurement, there is an increase in the capacity i.e from 180 mAh g-1 of bulk MnPS3 (BMPS) to 500 mAh g-1 of the EMPS. Using the Cyclic voltammetry and galvanotactic charging and discharging test, it is observed that the capacity profile remains stable. In the subsequent cycles, it indicates that the reaction has a reversibility process. Even after 200th cycle as can be seen in figure 12(d), the charge and discharge capacity stay close to the initial capacity which is about 500mA h g-1 for EMPS. Hence the properties are desirable in the application of LIB.